Spatial Memory and Gut Microbiota Alterations Are Already Present in Early Adulthood in a Pre-clinical Transgenic Model of Alzheimer’s Disease - Bello-Medina, Paola C.; Hernández-Quiroz, Fernando; Pérez-Morales, Marcel; González-Franco, Diego A.; Cruz-Pauseno, Guadalupe; García-Mena, Jaime; Díaz-Cintra, Sofía; Pacheco-López, Gustavo (Frontiers in Neuroscience, 2021)
The irreversible and progressive neurodegenerative Alzheimer’s disease (AD) is characterized by cognitive decline, extracellular β-amyloid peptide accumulation, and tau neurofibrillary tangles in the cortex and hippocampus. The triple-transgenic 3xTg mouse model of AD presents memory impairment in several behavioral paradigms and histopathological alterations from 6 to 16 months old. Additionally, it seems that dysbiotic gut microbiota is present in both, mouse models and patients of AD at the cognitive symptomatic stage. The present study aimed to assess spatial learning and memory retention, and gut microbiota alterations in an early-adult stage of the 3xTg-AD mice, and to explore its sexual dimorphism. We evaluated motor activity, novel-object localization training, and retention test, and collected fecal samples to characterize relative abundance, alpha and beta-diversity, and LefSe analysis in gut microbiota in both female and male 3xTg-AD mice, and controls NoTg, at 3 and 5 months old. We found spatial memory deficits in female and male 3xTg-AD, but no alteration neither during training nor in motor activity. Importantly, already at 3 months old we observed decreased relative abundances of Actinobacteria and TM7 in 3xTg-AD compared to NoTg mice, while the beta-diversity of gut microbiota was different in female and male 3xTg-AD mice in comparison to NoTg. Our results suggest that gut microbiota modifications in 3xTg-AD mice anticipate, and thus could be causally related to cognitive decline already at the early-adult age of AD. We propose that microbiota alterations may be used as an early and non-invasive diagnostic biomarker of AD.